Exploring the paths between fears of compassion and negative affect: The roles of external shame and self- criticism across men and women - Romão, Maria Ana Pereira Pais Foz (2017)
Dissertação de Mestrado Integrado em Psicologia apresentada à Faculdade de Psicologia e de Ciências da Educação